Euclinostomum heterostomum (Rudolphi, 1809) Metacercarial Infection in Three Osphronemid Fish Specieshree Osphronemid Fish Species - PURIVIROJKUL, Watchariya; SUMONTHA, Montri (Walailak Journal of Science and Technology (WJST), 2013)
Trematode metacercariae, Euclinostomum heterostomum from naturally infested osphronemid fish in Thailand were investigated. Encysted musculature was observed in the case of heavy infestation in all three osphronemid fish species, Trichopsis vittata, Betta splendens and Betta imbellis. Infected fish showed tubercle-like thickened areas of different size, 0.2 - 0.5 cm which appear on the skin. A histological study showed metacercaria were enclosed by a thin sheet of connective tissue. This is a new recorded host of E. heterostomum.